Let's solve the equation step by step.
-
Start with the equation: \[ -2.4x - 1.1 = 3.7 \]
-
Add \(1.1\) to both sides of the equation: \[ -2.4x = 3.7 + 1.1 \] So: \[ 3.7 + 1.1 = 4.8 \] Therefore, we have: \[ -2.4x = 4.8 \]
-
Now, divide both sides by \(-2.4\): \[ x = \frac{4.8}{-2.4} \] Calculating the division gives: \[ x = -2 \]
So, filling in the blanks:
- The first blank after \(-2.4x=\) is \(4.8\).
- The value of \(x\) is \(-2\).
Thus the completed solution is:
\[ -2.4x = 4.8 \]
\[ x = -2 \]